Electroencephalographic (EEG) density spectral array monitoring in children during sevoflurane anaesthesia: a prospective observational study. (27th October 2018) - de Heer, I. J.; Bouman, S. J. M.; Weber, F.
Summary: Electroencephalographic density spectral array monitoring has been developed to facilitate the interpretation of unprocessed electroencephalogram signals. The primary aim of this prospective observational study, performed in a tertiary children's hospital, was to identify the clinical applicability and validity of density spectral array monitoring in infants and children during sevoflurane anaesthesia. We included 104 children, aged < 6 years, undergoing elective surgery during sevoflurane anaesthesia. We investigated the correlation between non‐steady state end‐tidal sevoflurane and the expression of the four electroencephalogram frequency bands β, α, θ and δ, representing density spectral array. Patients were divided into three age groups (< 6 months, 6–12 months, > 12 months). There was a significant correlation between end‐tidal sevoflurane and density spectral array in the age groups 6–12 months (p < 0.05) and 1–6 years (p < 0.0001). In infants < 6 months of age, the relative percentages of density spectral array did not correlate with end‐tidal sevoflurane. The main finding was that different end‐tidal concentrations of sevoflurane produce age‐dependent changes in the density spectral array power spectrum. In infants younger than 6 months‐old, α and β coherence are absent, whereas θ and δ oscillations have already emerged. In cases where anaesthesia was too deep, this presented as burst suppression on the electroencephalogram, θ disappeared, leaving the electroencephalographic activity in the δ range. Future research should address this issue, aiming to clarify whether the emergence of θ oscillations in infants helps to prevent sevoflurane overdosing.